Between Faith and Tradition: Religious Moderation in West Sumatra's Muslim Families - Rama Dhini Permasari Johar; Zulkifli Zulkifli; Syalwa Azahra; Darwati Darwati; Miza Puspita Dewi (Jurnal Dialog, 2026)
This study aims to analyze the practice of religious moderation and the influence of Islamic tradition and law on the values ​​of moderation in traditional Muslim families in West Sumatra. This study employed a qualitative approach, with data collection techniques including in-depth interviews, observations, and documentation. The research informants imprised 23 parents from traditional Muslim families in the Tigo Lurah District, Solok Regency. Data analysis utilized Nvivo 12 software with thematic coding presented in a project map. The author also employed the theories of Religious Moderation and Legal Pluralism as analytical tools. The results show that religious moderation in traditional Muslim families is realized through a balance between adherence to religious teachings and respect for local customs. The values ​​of tolerance, deliberation, and moderation in religion are instilled through role models and dialogue within the family. The Nvivo 12 analysis demonstrates the strong interaction of religious law, customs, and social norms in family religious practices. Furthermore, informants expressed a preference for leaders of the same faith as part of the principles of religious law, without eliminating tolerance for differences. This research confirms that religious moderation in traditional Muslim families is contextual and rooted in local religious and cultural values.